Discovery and Investigation of Mutase-like Activity in a Phenylalanine Ammonia Lyase from Anabaena variabilis - Weise, Nicholas J. (Top Catal, 2018)
The effect of extended reaction times on the regio- and enantioselectivity of the phenylalanine ammonia lyase (PAL)-catalysed amination of a subset of cinnamate derivatives was investigated. This was done using a PAL from the cyanobacterium Anabaena variabilis and incubation in a concentrated ammonia buffer. Whilst early time point analyses revealed excellent selectivities to give mostly the well-documented (S)-α-amino acid products, subsequent accumulation of other regio-/stereo- isomers was seen. For many para-substituted substrates, the β-regioisomer, a previously-unreported product with this enzyme class, was found to become more abundant than the α-, after sufficient incubation, with slight preference for the (R)-enantiomer. Although attempts to tune the selectivity of the PAL toward any of the three side products were largely unsuccessful, the results provide insight into the evolutionary history of this class of enzymes and reinforce the prominence of the toolbox of specific and selective cinnamate-aminating enzymes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11244-018-0898-1) contains supplementary material, which is available to authorized users.